Assessment of Calcium Alginate Gels As Wall Materials For Encapsulation Systems - Orona, Jesica Daiana (2023)
BACKGROUND: Calcium alginate gels are widely used to encapsulate active compounds. Some characteristic parameters of these gels are necessary to describe the release of active compounds through mechanistic mathematical models. In this work, transport and kinetics properties of calcium alginate gels were determined through simple experimental techniques. RESULTS: The weight-average molecular weight ((Formula presented.) = 192 × 103 Da) and the fraction of residues of α-l-guluronic acid ((Formula presented.) = 0.356) of sodium alginate were determined by capillary viscometry and 1H-nuclear magnetic resonance at 25 °C, respectively. Considering the half egg-box model, both values were used to estimate the molecular weight of calcium alginate as (Formula presented.) = 2.02 × 105 Da. An effective diffusion coefficient of water ((Formula presented.) = 2.256 × 10−9 m2 s−1) in calcium alginate was determined using a diffusion cell at 37 °C. Finally, a kinetics constant of depolymerization ((Formula presented.) = 9.72 × 10−9 m3 mol−1 s−1) of calcium alginate was obtained considering dissolution of calcium to a medium under intestinal conditions. CONCLUSION: The experimental techniques used are simple and easily reproducible. The obtained values may be useful in the design, production, and optimization of the alginate-based delivery systems that require specific release kinetics of the encapsulated active compounds.